2013
DOI: 10.1214/12-aoas615
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian alignment of similarity shapes

Abstract: We develop a Bayesian model for the alignment of two point configurations under the full similarity transformations of rotation, translation and scaling. Other work in this area has concentrated on rigid body transformations, where scale information is preserved, motivated by problems involving molecular data; this is known as form analysis. We concentrate on a Bayesian formulation for statistical shape analysis. We generalize the model introduced by Green and Mardia for the pairwise alignment of two unlabeled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This raises concerns especially when the size of objects is the focal point of a study, such as in the study of rat skulls' growth described in Section 1, which was recently revisited by Mardia et al (2013) who carried out a Bayesian analysis with size being a key concept in their investigation. In the upcoming section, we derive unbiased score functions for the measurement error models formulated in Section 2, followed by estimating equations based on these scores.…”
Section: Bias Analysis In Three-dimensional Size-and-shape Matchingmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises concerns especially when the size of objects is the focal point of a study, such as in the study of rat skulls' growth described in Section 1, which was recently revisited by Mardia et al (2013) who carried out a Bayesian analysis with size being a key concept in their investigation. In the upcoming section, we derive unbiased score functions for the measurement error models formulated in Section 2, followed by estimating equations based on these scores.…”
Section: Bias Analysis In Three-dimensional Size-and-shape Matchingmentioning
confidence: 99%
“…A detailed description of the data of rat skulls brought up in Section 1 is given in Bookstein (1991). Besides Kenobi, Dryden, and Le (2010) and Mardia et al (2013), many researchers have analyzed the data assuming the recorded skull configurations are precise (Goodall and Lange 1989;Monteiro 1999;Le and Kume 2000;. For illustration purposes, we assume that the skull configurations, each consisting of eight landmarks, are contaminated with measurement error.…”
Section: Application To Real Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Green and Mardia () considered rigid body transformations in their applications, but Mardia et al . () demonstrated applications using full similarity transformations. Forbes et al .…”
Section: Mathematical Formulation: Unlabelled Shape Analysismentioning
confidence: 99%
“…The underlying formulation is very flexible. For instance, Green and Mardia (2006) consid-ered rigid body transformations in their applications, but Mardia et al (2013) demonstrated applications using full similarity transformations. Forbes et al (2014) also used this approach with similarity transformations in the context of fingerprint matching.…”
Section: Mathematical Formulation: Unlabelled Shape Analysismentioning
confidence: 99%